Recent advances in hybrid wet scrubbing techniques for NOx and SO2 removal: State of the art and future research. (June 2021) - Sharif, Hafiz Muhammad Adeel; Mahmood, Nasir; Wang, Shengye; Hussain, Ijaz; Hou, Ya-Nan; Yang, Li-Hui; Zhao, Xu; Yang, Bo
Abstract: Recently, the discharge of flue gas has become a global issue due to the rapid development in industrial and anthropogenic activities. Various dry and wet treatment approaches including conventional and hybrid hybrid wet scrubbing have been employing to combat against these toxic exhaust emissions. However, certain issues i.e., large energy consumption, generation of secondary pollutants, low regeneration of scrubbing liquid and high efficieny are hindering their practical applications on industrial level. Despite this, the hybrid wet scrubbing technique (advanced oxidation, ionic-liquids and solid engineered interface hybrid materials based techniques) is gaining great attention because of its low installation costs, simultaneous removal of multi-air pollutants and low energy requirements. However, the lack of understanding about the basic principles and fundamental requirements are great hurdles for its commercial scale application, which is aim of this review article. This review article highlights the recent developments, minimization of GHG, sustainable improvements for the regeneration of used catalyst via green and electron rich donors. It explains, various hybrid wet scrubbing techniques can perform well under mild condition with possible improvements such as development of stable, heterogeneous catalysts, fast and in-situ regeneration for large scale applications. Finally, it discussed recovery of resources i.e., N2 O, NH3 and N2, the key challenges about several competitive side products and loss of catalytic activity over time to treat toxic gases via feasible solutions by hybrid wet scrubbing techniques. Graphical abstract: Image 1 Highlights: A critical and detail discussion of traditional wet scrubbing with its limitations and solutions. Significance of hybrid wet scrubbing, recent innovations for simultaneous removal of air-pollutants. Newly developed low-cost and stable engineered interface green catalysts are presented. Utilization of hybrid-materials for the recovery of useful products from a waste gas.